Bilateral Posterior Fracture-Dislocation of the Shoulders Following Epileptic Seizures: A Case Report and Review of the Literature - Pushpakumara, J.; Sivathiran, S.; Roshan, L.; Gunathilake, S.B. (BioMed Central, 2015)
Background: Bilateral posterior fracture-dislocation of the shoulders is an uncommon complication of grand mal seizures. We report a case of bilateral posterior dislocation of the shoulders with proximal humeral fractures following epileptic seizures. A posterior fracture-dislocation of the shoulder is very rare and can be caused by epileptic seizures, trauma, electrocution or electroconvulsive therapy. Case presentation: A 62-year-old Sri Lankan male was admitted to our medical unit following four repeated generalized tonic-clonic convulsions, each lasting for several minutes. Following the second seizure he reported an inability to move both upper arms due to intense pain.There was no history of fall during the episodes'of convulsions however but the bystanders have forcibly restrained his movements during the tonic-clonic convulsions. Clinical examination revealed severely restricted range of movement in both shoulders, with associated swelling and bruising of the shoulder joints and upper arms. Radiographs of the shoulders confirmed fractures at the level of surgical neck with posterior dislocation. Conclusion: Bilateral posterior fracture-dislocation of shoulders complicating epileptic seizures are rare. Forcible restraining of the patient's upper limbs during seizures is the likely cause for the fracture dislocations in our patient and this had not been reported before.
Keywords: Bilateral fracture dislocation; Shoulders; Generalized seizures